Is widespread screening for hepatitis C justified?. (13th January 2015) - Koretz, Ronald L; Lin, Kenneth W; Ioannidis, John P A; Lenzer, Jeanne
Abstract : Several organisations have recommended greatly expanded screening for hepatitis C infection. Ronald Koretz and colleagues are concerned that no study has tested whether this will lead to net clinical benefit or harm in screened populations